G2P1A0H1 Gravid 27-28 Minggu + Janin Mati Kehamilan Abdominal - Fitriansyah, Irwin; Rifendra, Gerry (Fakultas Kedokteran Universitas Andalas, 2020)
Abdominal pregnancy is a rare form of pregnancy but presents a very high risk of both morbidity and mortality for the fetus and mother. This situation is one of the most serious forms of ectopic pregnancy. The incidence of abdominal pregnancy varies, Rahman et al, get an incidence of 1 in 130,200 births. In the United States between 1970-1983 there were 10.9 abdominal pregnancies / 100,000 live births and 9.2 abdominal pregnancies / 1000 ectopic pregnancies. In laparotomy, placental management is the most difficult challenge, because it must be well prepared and planned. In this case report a 36-year-old woman with a diagnosis of gravid G2P1A0H1 27-28 weeks + Abdominal Pregnancy + Dead Fetus + Mild Anemia. Laparotomy is performed to deliver the baby, Durante surgery is carried out exploration of the placental attachment. Obtained the placenta embedded in the douglas cavum by attaching to the Ascendent Colon, Rectum, descending colon, intestine and peritoneum. It appears that some of the placenta has detached from its implantation, accompanied by a pile of stout cells. Removal of the placenta was carried out throughout the attachment site. The rest of the placenta is cleaned one by one by clamping with the clam punster slowly. Keywords: Abdominal Pregnancy, Dead Fetus, Laparotomy